IL-23 in inflammatory bowel diseases and colon cancer - Neurath, Markus (Cytokine & Growth Factor Reviews, 2019)
Studies in recent years have identified a pivotal role of the cytokine IL-23 in the pathogenesis of inflammatory bowel diseases (IBD: Crohn's disease, ulcerative colitis) and colitis-associated colon cancer. Genetic studies revealed that subgroups of IBD patients have single nucleotide polymorphisms in the IL-23R gene suggesting that IL-23R signaling affects disease susceptibility. Furthermore, increased production of IL-23 by macrophages, dendritic cells or granulocytes has been observed in various mouse models of colitis, colitis-associated cancer and IBD patients. Moreover, in several murine models of colitis, suppression of IL-12/IL-23 p40, IL-23 p19 or IL-23R function led to marked suppression of gut inflammation. This finding was associated with reduced activation of IL-23 target cells such as T helper 17 cells, innate lymphoid cells type 3, granulocytes and natural killer cells as well as with impaired production of proinflammatory cytokines. Based on these findings, targeting of IL-23 emerges as important concept for suppression of gut inflammation and inflammation-associated cancer growth. Consistently, neutralizing antibodies against IL-12/IL-23 p40 and IL-23 p19 have been successfully used in clinical trials for therapy of Crohn's disease and pilot studies in ulcerative colitis are ongoing. These findings underline the crucial regulatory role of IL-23 in chronic intestinal inflammation and colitis-associated cancer and indicate that therapeutic strategies aiming at IL-23 blockade may be of key relevance for future therapy of IBD patients.
CRIS-Team WoS Importer:2019-03-20